answersLogoWhite

0


Best Answer

-6z 2 = 3z+ 4z+28

-6z+2 +3z = 3z+ 4z +28 +4z

-6z+4z+2 = 3z+ 28

-10z+2 -3z= 28 - 2

-10z + -3z = 26

-13z/13 = 26/-13

z = -2

User Avatar

Wiki User

โˆ™ 2012-09-03 10:19:49
This answer is:
User Avatar
Study guides

Algebra

20 cards

A polynomial of degree zero is a constant term

The grouping method of factoring can still be used when only some of the terms share a common factor A True B False

The sum or difference of p and q is the of the x-term in the trinomial

A number a power of a variable or a product of the two is a monomial while a polynomial is the of monomials

โžก๏ธ
See all cards
3.79
โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…โ˜†โ˜…
1456 Reviews

Add your answer:

Earn +20 pts
Q: -6z plus 2 equals 3z plus 4z plus 28 How do you prove the answer -2 is correct?
Write your answer...
Submit
Still have questions?
magnify glass
imp
People also asked